1985
DOI: 10.1177/000841748505200403
|View full text |Cite
|
Sign up to set email alerts
|

The Supervisor-Student Ratio: 1:1 versus 1:2

Abstract: Although an instructor-student ratio of 1:1 is widely accepted and officially sanctioned by educators of occupational therapists, there is no reported experience with other ratios which can serve as a basis of comparision. This study explores the advantages and disadvantages of the 1:2 ratio in clinical supervision, first as anticipated by the supervising therapists (STs), and then as perceived by them and by their students after a trial experience. Results indicated that (a) although STs anticipated only disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 5 publications
1
33
0
Order By: Relevance
“…Various models of flexible fieldwork education have been described over the past 15 years. Examples of these include role-emerging placements (Bossers et al, 1997;Huddleston, 1999b), group supervision (Jung et al, 1994;Mason, 1998Mason, , 1999, two students to one supervisor (Tiberius and Gaiptman, 1985;Edwards, 1998, Huddleston, 1999b), four students to one supervisor (Zakrzewski and Salonga, 1997), split placements (Gaiptman and Forma, 1991) and long-arm supervision (Alsop and Ryan, 1996). Many Australian and international occupational therapy programmes are offering alternative fieldwork placements across different areas of occupational therapy practice.…”
Section: External Impacts On Fieldwork Provisionmentioning
confidence: 99%
“…Various models of flexible fieldwork education have been described over the past 15 years. Examples of these include role-emerging placements (Bossers et al, 1997;Huddleston, 1999b), group supervision (Jung et al, 1994;Mason, 1998Mason, , 1999, two students to one supervisor (Tiberius and Gaiptman, 1985;Edwards, 1998, Huddleston, 1999b), four students to one supervisor (Zakrzewski and Salonga, 1997), split placements (Gaiptman and Forma, 1991) and long-arm supervision (Alsop and Ryan, 1996). Many Australian and international occupational therapy programmes are offering alternative fieldwork placements across different areas of occupational therapy practice.…”
Section: External Impacts On Fieldwork Provisionmentioning
confidence: 99%
“…Supervision strategies were identified in a study by Tiberius and Gaiptman (1985) on a 1:2 supervisor:student ratio model in occupational therapy fieldwork education. They included the use of learning contracts, the provision of individual feedback as required, clarifying the roles that students are expected to take when working with clients, defining the ground rules for interaction with clients, and encouraging students to share ideas with their supervisors and to provide mutual constructive feedback.…”
Section: Group Models In Occupational Therapy Fieldworkmentioning
confidence: 99%
“…A study carried out in Canada (Tiberius and Gaiptman 1985) revealed that occupational therapy students and supervisors anticipated mainly disadvantages before a 1:2 placement, although their view changed after the event. There is an assumption that 1:2 placements will double the workload of the fieldwork educator and halve the quality of the student's experience.…”
Section: Introductionmentioning
confidence: 99%